2021
DOI: 10.1101/2021.05.24.445510
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

CmP signaling network unveils novel biomarkers for triple negative breast cancer in African American women

Abstract: Breast cancer is the most commonly diagnosed cancer worldwide and remains the second leading cause of cancer death. While breast cancer mortality has steadily declined over the past decades through medical advances, an alarming disparity in breast cancer mortality has emerged between African American women (AAW) and Caucasian American women (CAW); and new evidence suggests more aggressive behavior of triple-negative breast cancer (TNBC) in AAW may contribute to racial differences in tumor biology and mortality… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

5
0

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 184 publications
(103 reference statements)
0
4
1
Order By: Relevance
“…Since nPR-mediated signaling pathways usually have protective roles over the CSC, the intricate balance of the CmPn signaling network is more stable under mPR-specific PRG actions compared to the CmP network. Therefore, in contrast to our previously observed nPR(+) breast cancer and nPR(-) endothelial cell data ( 57 , 89 , 92 ), mPR-specific PRG actions have variable effects on both RNA and protein expression levels on the CSC in TNBCs, which can be utilized for subtype classifications ( 90 , 91 ). In general, the relationships among the CSC, mPRs, PRG, nPRs, and their mediated signaling pathways within either the CmPn or the CmP signaling networks can be summarized ( Figure 1 ).…”
Section: Cmpn/cmp Signaling Networkcontrasting
confidence: 70%
See 4 more Smart Citations
“…Since nPR-mediated signaling pathways usually have protective roles over the CSC, the intricate balance of the CmPn signaling network is more stable under mPR-specific PRG actions compared to the CmP network. Therefore, in contrast to our previously observed nPR(+) breast cancer and nPR(-) endothelial cell data ( 57 , 89 , 92 ), mPR-specific PRG actions have variable effects on both RNA and protein expression levels on the CSC in TNBCs, which can be utilized for subtype classifications ( 90 , 91 ). In general, the relationships among the CSC, mPRs, PRG, nPRs, and their mediated signaling pathways within either the CmPn or the CmP signaling networks can be summarized ( Figure 1 ).…”
Section: Cmpn/cmp Signaling Networkcontrasting
confidence: 70%
“…The interplays between classic and non-classic PRG-mediated signaling have been long suspected ( 43 , 44 , 49 , 99 ) and newly discovered evidence demonstrated that the CSC plays an essential role to bridge crosstalk among nPRs, mPRs, and their ligands to form the CmPn/CmP signaling networks in response to mPR-specific PRG actions among nPR(+/-) breast cancer cells ( 57 , 90 , 91 , 93 ). The convergence of classic and non-classic PRG actions by the CSC on their common ligands and downstream cellular targets in breast cancer cells is an attractive model by which mPR-specific PRG actions play a central role for the stability of this system by fine-tuning the intricate balance within CmPn/CmP signaling network.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations